Reconceptualising intracareer transitions as coach-becomings: a rhizomatic narrative case study of an American basketball coach - Darpatova-Hruzewicz, D.; Book, R. T., Jr.; Khomutova, A. (International Sport Coaching Journal, 2025)
This paper offers a poststructuralist exploration of the career transitions of an American basketball coach into and within collegiate basketball. We draw on the theory of Deleuze and Guattari to reconceptualise coaching transitions as coach-becomings contrasted with humanist conceptions of outcome-centred, staged processes. Our nomadic analysis is based on longitudinal interviews and ethnographic data collected over a 4-year period. We adopt narrative rhizomatics and ventriloquism to examine the coaching and institutional assemblages engaged in the production of coaching beliefs and behaviours in specific transition contexts. We also attend to the dialogical and performative aspects of analysis in relation to the role of researchers. Our findings suggest that collegiate environments are conducive to disciplinary coaching practices framed within discourses of masculine militarism and dualist representationalism, thus adversely impacting learning, development, and adaptability in transition. We argue that an alternative conceptualisation of transitions as coach-becomings shifts the focus away from arborescent unitary logic to more creative, nonlinear pedagogies that embrace multiplicity and fluidity. Engaging with the Deleuzian ontology of difference also implies raising awareness of coaching as a social and political practice.